Bi-leaflet venous valve : computer aided design - Hu, Hewen (Nanyang Technological University, 2020)
Chronic venous insufficiency (CVI) is a condition whereby the venous valves fail to function as intended and this results in retrograde blood flow. This affects the efficiency of blood flowing from the lower extremities of the human limbs back to the heart. There is a need to design a setup which mimics the muscle pump effect. This will supplement the efforts in the design of new prosthetic venous valves which aims to replace diseased ones in the human body. In this report, the steps to programming and designing the muscle pump setup are presented, as well as some tests to modified conduits, so that they are more suitable for use in the setup. Results from this project show that the setup is able meet the requirements of compressing the conduit in a manner similar to forces exerted by skeletal muscles on venous veins. In this project, a throttle is being used to control the airflow from the outlet, and manual adjustments are needed to prevent excess pressure from building up. However, some fine tuning is required to make the setup more portable and automated.